Interleukin-1β Accelerates the Onset of Stroke in Stroke-Prone Spontaneously Hypertensive Rats - Tsuyoshi Chiba; Tatsuki Itoh; Masaki Tabuchi; Toru Nakazawa; Takao Satou (Mediators of Inflammation)
High blood levels of inflammatory biomarkers and immune cells in stroke lesions have been recognized as results of stroke. However, recent studies have suggested that inflammation occurs prior to stroke onset. In this study, we aimed to clarify the role of inflammation in stroke onset among stroke-prone spontaneously hypertensive rats (SHRSP). At 4 weeks of age (before stroke onset), the plasma level of IL-1β was significantly higher in SHRSP (153.0±49.7 pg/ml) than in Wistar Kyoto rats (WKY) (7.7±3.4 pg/ml, P<0.001 versus SHRSP) or spontaneously hypertensive rats (SHR) (28.0±9.1 pg/ml, P<0.001 versus SHRSP) (n=6 per strain). Stimulated IL-1β signal was also observed in cerebrovascular endothelial cells of SHRSP. Gene expressions of IL-1β, IL-1 receptors, caspase-1, and downstream genes (MCP-1 and ICAM-1), which associated with immune cell recruitment, were significantly greater in SHRSP than in WKY or SHR, coincident with greater NFκB protein levels in SHRSP compared to WKY or SHR. In addition, continuous administration of IL-1β (2 μg/day) using an osmotic pump slightly increased the incidence of stroke in SHR (P=0.046) and significantly accelerated the onset of stroke in SHRSP (P=0.006) compared to each control (n=10 per group). These results suggest that a stimulated IL-1β signal might be a cause of stroke onset when concomitant with severe hypertension.